RANCANG BANGUN SISTEM INFORMASI DATA LAPORAN KEPOLISIAN UNIT PENCURIAN MOTOR BERBASIS ANDROID - Tella, Fitriyani; Setyawan, Muhammad Rizki; Soekarta, Rendra; Sari, Novita (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2024)
The level of motorbike theft cases in Sorong Regency is quite high, it is known that in 2022 there will be around 91 cases. The factors that cause motorbike theft can be identified from economic, environmental, educational and individual background factors. The perpetrators of theft always have reasons behind the theft, including seeking profit, fulfilling needs, and there are also those who do it because of the opportunity. Extreme Programing (EP) is a simple software development method and includes one of the agile methods pioneered by Kent Beck, Ron Jeffries, and Ward Cunningham. The reason the author uses this method is because of the nature of the application which is developed quickly through stages including Planning, Design, Coding, and Testing. Meanwhile, the testing method used is the Blackbox Testing method. From the results of application testing and usability testing, the researcher carried out Usability Testing calculations, the interpretation score obtained was more than 60% with the statement AGREE, where the highest score was 71.4% with the statement STRONGLY AGREE, so it can be concluded that the creation of an information system application Android based is in accordance with what the user wants